Camins de Viaur dins los romans occitans de Ferran Delèris - Claire Torreilles (Lengas)
In his novel Pèire e Marià, Ferran Delèris (1922-2009) born on the Segala plateau that dominates the Viaur valley (Rouergue), depicts a young country couple that the war is going to keep apart in 1917 and 1918. As the chain of events unfolds, the reader is captivated by the description of the landscape that the author knew as a child because it is more than a scenery. The Viaur valley is lived through, it is haunted by legends while the characters – Marià most of all –, become outstanding personalities.